(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action or both. The present study tested the anti-diabetic and hypolipidemic potential of pterostilbene isolated from Pterocarpus marsupium plants on high fat diet-induced diabetic rats. The high-fat diet-fed rats showed increased serum glucose, cholesterol, triglycerides and insulin resistance (p < 0.05). However, treating the animals with pterostilbene different biochemical parameters like glucose tolerance, glycogen content, glucose homeostatic enzymes like glucose-6-phosphatase and hexokinase, adipocytes differentiation, and the expression profiles of different genes regulating carbohydrate and lipid metabolism were improved significantly (p < 0.05). Further, pterostilbene was found to demonstrate dual regulation activities for peroxisome proliferators-activated receptors (PPAR) (both PPARα and PPARγ). In conclusion, these results show that pterostilbene acts as a potent anti-diabetic molecule. Hence further in-depth mechanistic studies are warranted to use this phytochemical as a medicine.